Steady-state and transient performance of a series excited synchronous motor - Özdemir, M; Bayindir, MI; Önbilgin, G (Emerald, 2002)
This study involves the development of a PSPICE 5.4 package oriented model for the dynamic behaviour of a series excited synchronised slip ring induction motor including the bridge rectifier for rotor circuit excitation. Furthermore, in this study is aimed at investigating the synchronising behaviour for various rotor connections of a series excited synchronous motor formed by connecting a bridge rectifier input in series with the stator winding of a slip-ring induction motor whereas the rectifier output feeds the rotor winding. The steady state behaviour of such a scheme in comparison to a separately excited one is wed known, but the behaviour during synchronisation requires further study. Presentation of results obtained by a PSPICE based simulation and comparison with experimental results acquired during this study points to a model to account for design variations and additional circuitry. It is convenient to use this model in a drive system. The advantage of this simulation method over the others is that it does not involve the utilisation of specialised programs and mathematical difficulties such as the solution of stiff differential equations. Furthermore, steady state behaviour of the scheme is explained by means of a simple analysis and illustrated by test results.
Keywords: induction motor; model; PSPICE